The effect of crystallographic mismatch on the obstacle strength of second phase precipitate particles in dispersion strengthening: bcc Nb particles and nanometric Nb clusters embedded in hcp Zr. (1st January 2016) - Matsukawa, Y.; Yang, H.L.; Saito, K.; Murakami, Y.; Maruyama, T.; Iwai, T.; Murakami, K.; Shinohara, Y.; Kido, T.; Toyama, T.; Zhao, Z.; Li, Y.F.; et al.
Abstract: A potential factor dominating the obstacle strength of second phase precipitate particles in dispersion strengthening is the crystallographic mismatch between the matrix phase and the second phase; however, yet this concept has not been fully assessed by experiments and simulations. In the present study, we experimentally investigated the obstacle strength of body centered cubic (bcc) Nb particles and nanometric Nb clusters embedded in hexagonal close packed (hcp) Zr matrix. The bcc Nb is softer than the hcp Zr in terms of shear modulus, whereas from a crystallographic viewpoint, the bcc Nb particles can be nonshearable, strong obstacles because the slip plane inside the particles is not parallel with that in the matrix. Although the bcc Nb is thermodynamically the stable configuration for Nb atoms precipitating from the Zr matrix, in the very early stage of solute agglomeration, the crystal structure of Nb nanoclusters is possibly hcp rather than bcc. The obstacle strength ( α ) was no greater than 0.5 for the Nb nanoclusters, whereas 0.85 ≤ α ≤ 1 for the coarse bcc Nb particles; α = 1 was obtained with the Taylor factor ( M ) of 5.5 and α = 0.85 with M = 6.5, respectively. These results indicate that the bcc Nb particles are strong obstacles, and that the Nb nanoclusters are weak obstacles. Graphical abstract: